ANALISIS KOMPETENSI SOSIAL GURU MATA PELAJARAN IPS TERPADU KELAS VII DI SMP NEGERI 10 PONTIANAK - Analia, Vitri; Noor, Agus Sastrawan; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThis study aims to determine the teacher's understanding in applying the social competency of socia studies subject teachers in grade VII. The research method used is descriptive in the form of qualitative research. Sources of research data are vice principals, teachers and students. The results of the study with five indicators formulating the problem show that the teacher's understanding in applying teacher competence, especially the social competence of teachers in the school environment as a whole is quite good, such as the ability of teachers to communicate with students is quite good, although not too effective, already very good, the teacher's ability to collaborate with BP3 teachers is good, the ability of teachers to associate with fellow workers and education partners is very good and the ability of teachers to understand the surrounding world is good so that overall social studies teachers understand and apply social competence in the school environment already well.Â Keywords: Social Competence and Social Sciences Subjects.